Educating the net generation : implications for learning and teaching in Australian universities : final report. - Bennett, Sue; Bishop, Andrea; Chang, Rosemary; Dalgarno, Barney; Gray, Kathleen; Judd, Terry; Kennedy, Gregor; Krause, Kerri-Lee; Maton, Karl; Waycott, Jenny (Australian Learning and Teaching Council, 2009)
Final report from a project that sought to identify the implications of educating the 'Net Generation' for learning and teaching in Australian universities. The project was carried out at three institutions (The University of Melbourne, the University of Wollongong and Charles Sturt University), and was conducted in three phases: Investigation, Implementation and Dissemination. The aim of the Investigation was to explore and document how university students and their teachers are using both established and emerging technologies to support their day-to-day activities and as learning and teaching tools. It consisted of an extensive literature review, a quantitative survey of students' and staff experiences with and preferences for a range of technologies, and a qualitative investigation involving a series of interviews and focus group sessions in which more detailed information about students' and staff views of technology was collected.